2013
DOI: 10.4161/cc.23825
|View full text |Cite
|
Sign up to set email alerts
|

TRIM16 inhibits neuroblastoma cell proliferation through cell cycle regulation and dynamic nuclear localization

Abstract: Neuroblastoma is the most common solid tumor in childhood and represents 15% of all children’s cancer deaths. We have previously demonstrated that tripartite motif 16 (TRIM16), a member of the RING B-box coiled-coil (RBCC)/tripartite totif (TRIM) protein family, has significant effects on neuroblastoma proliferation and migration in vitro and tumorigenicity in vivo. However, the mechanism by which this putative tumor suppressor influences cell proliferation and tumorigenicity was undetermined. Here we show, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…Another estrogen-responsive protein, TRIM16, which inhibits hepatocellular carcinoma cell migration and invasion by suppression of ZEB2 expression as well as suppresses cancer cell viability by involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016), is also up-regulated in glioma cells without IRE1 signaling enzyme function. Moreover, TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and induces apoptosis via activation of caspase-2 (Bell et al 2013;Kim et al 2013). Th erefore, our results conform to data that FAM162A, PGRMC2, TRIM16, and SLC39A6 have mainly anti-proliferative functions through interaction with diff erent transcription coregulators and signaling pathways of ER stress in cell specifi c manner.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Another estrogen-responsive protein, TRIM16, which inhibits hepatocellular carcinoma cell migration and invasion by suppression of ZEB2 expression as well as suppresses cancer cell viability by involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016), is also up-regulated in glioma cells without IRE1 signaling enzyme function. Moreover, TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and induces apoptosis via activation of caspase-2 (Bell et al 2013;Kim et al 2013). Th erefore, our results conform to data that FAM162A, PGRMC2, TRIM16, and SLC39A6 have mainly anti-proliferative functions through interaction with diff erent transcription coregulators and signaling pathways of ER stress in cell specifi c manner.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, recently was shown that TRIM16 inhibits cancer cell viability by a novel mechanism involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016). Th ere is also data that TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and melanoma cells proliferation and migration through regulation of interferon beta 1 as well as induces apoptosis through activation of caspase-2 in cancer cells (Bell et al 2013;Kim et al 2013;Sutton et al 2014).…”
mentioning
confidence: 99%
“…45 Some other members travel between the cytosol and nucleus to exert their functions. 46,47 In this study, we have found that the expression of MG53 is markedly increased in several animal models with metabolic disorders, although the underlying mechanism remains elusive. Candidate mechanisms may include changes in nutrients or genetic defects, or dysregulation of transcription factors or noncoding RNAs under pathological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The unlimited proliferation of cancer cells is often due to disorders of the cell cycle [23,24]. Our research team previously reported that knockdown of lncRNA AATBC resulted in inhibited bladder cancer cell proliferation through cell cycle arrest [25].…”
Section: Discussionmentioning
confidence: 99%